2014
DOI: 10.5194/amtd-7-1645-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The added value of a visible channel to a geostationary thermal infrared instrument to monitor ozone for air quality

Abstract: Abstract. Ozone is a tropospheric pollutant and plays a key role in determining the air quality that affects human wellbeing. In this study, we compare the capability of two hypothetical grating spectrometers onboard a geostationary (GEO) satellite to sense ozone in the lowermost troposphere (surface and the 0–1 km column). We consider one week during the Northern Hemisphere summer simulated by a chemical transport model, and use the two GEO instrument configurations to measure ozone concentration (1) in the t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These products, as shown in Fig. 15, have been developed using either OMI measurements alone or in conjunction with other satellite measurements to improve sensitivity to near-surface ozone (e.g., Bowman, 2013;Cuesta et al, 2013;Hache et al, 2014) as summarized below. They have been used in tropospheric research (e.g., Sauvage et al, 2007;Ziemke et al, 2010;Cooper et al, 2014), for example to show evidence of decadal increases or trends in global tropospheric ozone, El Nino events during Aura (e.g., Chandra et al, 2009;Blunden and Ardnt, 2016), the 1-2 month Madden-Julian oscillation , and references therein), and urban pollution (Kar et al, 2010).…”
Section: Tropospheric Ozone From Omi: Overview Of Different Methodsmentioning
confidence: 99%
“…These products, as shown in Fig. 15, have been developed using either OMI measurements alone or in conjunction with other satellite measurements to improve sensitivity to near-surface ozone (e.g., Bowman, 2013;Cuesta et al, 2013;Hache et al, 2014) as summarized below. They have been used in tropospheric research (e.g., Sauvage et al, 2007;Ziemke et al, 2010;Cooper et al, 2014), for example to show evidence of decadal increases or trends in global tropospheric ozone, El Nino events during Aura (e.g., Chandra et al, 2009;Blunden and Ardnt, 2016), the 1-2 month Madden-Julian oscillation , and references therein), and urban pollution (Kar et al, 2010).…”
Section: Tropospheric Ozone From Omi: Overview Of Different Methodsmentioning
confidence: 99%
“…However, under typical midlatitude conditions, O 3 in the planetary boundary layer (PBL, the mixed layer that extends 1–3 km above Earth's surface) can contribute anywhere from 10 to 50% to the total tropospheric column, and substantial variability in upper tropospheric O 3 can make it difficult to attribute changes in the total tropospheric column to changes in PBL O 3 [ Martins et al , ; Thompson et al , ]. Model simulations have suggested that multispectral retrieval techniques have the potential to derive a lower tropospheric or boundary layer O 3 column density, but these techniques cannot be implemented by using the current constellation of air quality‐relevant satellites [ Natraj et al , ; Zoogman et al , ; Hache et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Several OSSEs have been performed to assess the benefit of additions to the GOS to monitor air quality at the surface and lower troposphere (between the surface and ∼6 km), notably from GEO platforms. These OSSEs have tended to focus on measurements of ozone and CO (Edwards et al, 2009;Claeyman et al, 2011;Sellitto et al, 2013;Yumimoto, 2013;Hache et al, 2014;Zoogman et al, 2014); ozone is considered because it is a key lower tropospheric pollutant, and CO because it provides information on sources of pollution and transport processes in the lower troposphere. Other OSSEs for air quality have considered measurements of PM, another key tropospheric pollutant (Timmermans et al, 2009a,b).…”
Section: Observing System Simulation Experiments For Monitoring Air Qmentioning
confidence: 99%